Analisis Pengembangan Aplikasi Augmented Reality Untuk Pengenalan Organ Pernapasan Manusia - Lestari, Ayu; Trisnadoli, Anggy; Dewi, Meilany (STMIK Budi Darma, 2019)
A human respiratory organ is a vital tool in the human body. But until now most learning media only use torso as a teaching aid, learning module and pictures to display objects of respiratory organs to students. It is also not possible to see some of these objects directly. One of them is like human breathing learning material. Breathing or so-called respiration is an event that the body lacks oxygen (O2) and then oxygen outside the body is inhaled (inspired) through the respiratory organs. However, not many students know the human breathing organ is actually. Some only know from media images such as encyclopedia books. The existence of Augmented Reality technology will be very useful for the process of recognition of human respiratory organs in the form of three-dimensional objects. The application of human respiratory organs helps children to be able to learn independently at home so that children can learn in detail about the human respiratory organs. For this reason, an Augmented Reality introduction to human respiratory organs based on Android was made as a substitute for learning media for pictures and books that will display human respiratory organs and related information in them. With this application, it is expected to be able to introduce breathing organs to elementary school students in a more real form in three dimensions. Researchers design and build Educational augmented reality applications with the Markerless Augmented Reality method. The application is built using Blender as modeling, Adobe Photoshop, Audacity, Unity3D, Visual Studio, Vuforia SDK to form Augmented Reality